Recueil des sources arabes concernant l'Afrique occidentale du VIIIe au XVIe siècle: Bilād al-Sūdān - Cuoq, Joseph (Sources d'histoire médiévale, 1975)
Pp. 55-56: extract from Ibn al-Saghīr: Tarīkh al-Aīmma al-Rustamiyyīn; 123-124: extract from Abū Zak. Ya1yà al-Warjlanī: K. al-Sīra wa-Akhbar al-Aīmma; 166-168: extract from Abū 'l-Rabīʿ Sul. al-Wisyanī: Siyar al- Wisyanī; 171-175: extract from Anonymous: Siyar al-Mashayikh; 194-196: extract from Darjīnī: Tabaqat al- Mashayikh.
Keywords: Commerce transsaharien

The Myth of Trans-Saharan Trade during the Roman Era - Swanson, John T. (The International Journal of African Historical Studies, 1975)
Keywords: Commerce transsaharien

العلاقات التجارية بين المغرب والسودان عبر الصحراء من القرن 6 الى القرن 8ه ودور تلمسان فى هذا الميدان - عطا الله, دهينة (الأصالة, 1975)
Keywords: Commerce transsaharien